Redesain Tempat Pembuangan Sampah Sementara Manukan Kulon Menjadi Tempat Pengolahan Sampah Reduce, Reuse, Recycle (TPS 3R) - Erditya Fauzan Thoriqul Haqq; Euis Nurul Hidayah (INSOLOGI: Jurnal Sains dan Teknologi, 2022)
Garbage is still a problem experienced by the community, due to poor management and processing and lack of awareness of the community itself. The waste generated by the Manukan Kulon TPS is still managed conventionally. Garbage is temporarily stored and then disposed of to the landfill using a garbage truck. One of the efforts that can be done in order to overcome the waste problem is to redesign the Manukan Kulon Temporary Disposal Site into a Reduce, Reuse, Recycle (TPS 3R) so that the burden of waste that is accommodated in the TPA is reduced. This plan projects the age of the 3R TPS for the next ten years, so that the highest volume of waste generation in 2022 will reach 78.53 m3/day with a population served by 13,744 people. Planning The 3R TPS consists of a sorting area, a stall packaging area, an organic waste storage and enumeration area, an organic waste composting area, a leachate storage area, and a compost sieving and packaging area, and is equipped with an office, cart parking area, residue area, storage warehouse. tools, toilets and prayer rooms with a total building area of ​​527.75 m2. The budget plan (RAB) that must be spent for this plan is Rp. 1,080,200,973.